The radial expansion of the Diego blood group system polymorphisms in Asia: mark of co-migration with the Mongol conquests. (January 2019) - Petit, Florence; Minnai, Francesca; Chiaroni, Jacques; Underhill, Peter; Bailly, Pascal; Mazières, Stéphane; Costedoat, Caroline
Abstract Red cell polymorphisms can provide evidence of human migration and adaptation patterns. In Eurasia, the distribution of Diego blood group system polymorphisms remains unaddressed. To shed light on the dispersal of the Dia antigen, we performed analyses of correlations between the frequencies ofDI*01 allele, C2-M217 and C2-M401 Y-chromosome haplotypes ascribed as being of Mongolian-origin and language affiliations, in 75 Eurasian populations includingDI*01 frequency data from the HGDP-CEPH panel. We revealed thatDI*01 reaches its highest frequency in Mongolia, Turkmenistan and Kyrgyzstan, expanding southward and westward across Asia with Altaic-speaking nomadic carriers of C2-M217, and even more precisely C2-M401, from their homeland presumably in Mongolia, between the third century BCE and the thirteenth century CE. The present study has highlighted the gene-culture co-migration with the demographic movements that occurred during the past two millennia in Central and East Asia. Additionally, this work contributes to a better understanding of the distribution of immunogenic erythrocyte polymorphisms with a view to improve transfusion safety.